120k views
1 vote

\rm\sum_(n = 1)^ \infty ( - 1 {)}^(n - 1) \frac{ {\pi }^(2n + 1) }{(2n - 1)!(2n + 1)} \\

User Nsk
by
4.9k points

1 Answer

5 votes

Let


\displaystyle f(x) = \sum_(n=1)^\infty (-1)^(n-1) (x^(2n-1))/((2n-1)! (2n+1))

The exponent is indeed
2n-1 - not a typo!

Take the antiderivative of
f, denoted by
F. This recovers a factor of
2n in the denominator, which lets us condense it to a single factorial.


\displaystyle F(x) = \int f(x) \, dx = C + \sum_(n=1)^\infty (-1)^(n-1) (x^(2n))/((2n+1)!)

Recall the series expansion of sine,


\displaystyle \sin(x) = \sum_(n=0)^\infty (-1)^n (x^(2n+1))/((2n+1)!)

Then with a little algebraic manipulation, we get


\displaystyle F(x) = \int f(x) \, dx = C + 1 - \frac{\sin(x)}x

Differentiate to recover
f.


f(x) = (\sin(x) - x\cos(x))/(x^2)

Finally,
f(\pi) = \frac1\pi, so our sum is


\displaystyle \pi^2 f(\pi) = \sum_(n=1)^\infty (-1)^(n-1) (\pi^(2n+1))/((2n-1)! (2n+1)) = \boxed{\pi}

User Sam Day
by
5.3k points